Symbiosis with and mimicry of corals were facilitated by immune gene loss and body remodeling in the pygmy seahorse - Meng Qu; Yingyi Zhang; Joost Woltering; Yali Liu; Zixuan Liu; Shiming Wan; Han Jiang; Haiyan Yu; Zelin Chen; Xin Wang; Zhixin Zhang; Geng Qin; et al. (Proceedings of the National Academy of Sciences, 2025)
A remarkable example of symbiosis involves the pygmy seahorse ( Hippocampus bargibanti ). It lives obligatorily on gorgonian corals, mimicking their polyps with pink coloration and skin protuberances. Unique for seahorses, pygmy seahorses retain juvenile paedomorphic stunted snouts, resembling the coral’s polyps. We analyzed the tiny seahorse’s genome revealing the genomic bases of several adaptations to their mutualistic life including substantial reductions in conserved noncoding elements that are associated with genes in the vicinity of those CNEs that are known to play a role in growth and metamorphosis-related pathways. Comparative RNA- and ATAC-Seq analyses during their ontogeny suggest that their stunted snout might result from craniofacial remodeling associated with hoxa2b defunctionalization. This is consistent also with findings from in situ hybridization and CRISPR experiments. Their immune system shows extremely low numbers of MHC genes and additional considerable losses of other immune-related genes. This is likely facilitated by the host coral’s antimicrobial metabolites and by the earlier evolution of male pregnancy that requires immunotolerance.